2018
DOI: 10.1111/jog.13658
|View full text |Cite|
|
Sign up to set email alerts
|

Conservative surgery of uterine adenomyosis via laparoscopic versus laparotomic approach in a single institution

Abstract: Conservative surgery is effective to reduce the symptoms of adenomyosis regardless of approach method. For near-complete excision of adenomyosis, the diffuse type is recommended to be treated with laparotomic adenomyomectomy, and focal lesions less than 5 cm can be treated with laparoscopic conservative surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Our current results showed that the effective rate was almost 100% within 2 years after laparoscopic or laparotomic adenomyomectomy by using the modified double-flap method in patients with severe diffuse uterine adenomyosis, which confirmed our previous results 1. Recently, one study by Kwack et al showed that dysmenorrhea was improved in 100% of the patients with diffuse uterine adenomyosis at the 7-month follow-up after adenomyomectomy using the muscle fold method 23. Another study by Jun-Min et al found that the effective rate was 94.9% in patients with diffuse uterine adenomyosis within 2 years after the U-shaped adenomyomectomy 24.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our current results showed that the effective rate was almost 100% within 2 years after laparoscopic or laparotomic adenomyomectomy by using the modified double-flap method in patients with severe diffuse uterine adenomyosis, which confirmed our previous results 1. Recently, one study by Kwack et al showed that dysmenorrhea was improved in 100% of the patients with diffuse uterine adenomyosis at the 7-month follow-up after adenomyomectomy using the muscle fold method 23. Another study by Jun-Min et al found that the effective rate was 94.9% in patients with diffuse uterine adenomyosis within 2 years after the U-shaped adenomyomectomy 24.…”
Section: Discussionsupporting
confidence: 89%
“…However, the long-term efficacy of adenomyomectomy is rarely reported. Although there are long-term data in the literature, the evaluation of efficacy is still short term 18,23. Our results showed that although the therapeutic efficacy was decreased with the prolongation of postoperative time after laparoscopic or open adenomyomectomy, yet, the effective rate was both more than 60.0% at 6-year follow-up after surgery.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…As the myometrium of each flap is placed on top of each other and sutured together, this optimizes wound healing and may theoretically strengthen the myometrium to prevent future rupture. 8,9 Each layer is closed with a delayed absorbable suture in a running fashion until all dead space has been reapproximated. This is a complex, technically challenging procedure when performed laparoscopically or abdominally, and reports have largely come from high-volume centers.…”
Section: Surgical Techniquementioning
confidence: 99%